Improving bioaerosol exposure assessments 1 - comparative modelling of 2 emissions from different compost ages and activities. - Taha, Mohd Pauze M.; Drew, Gillian H.; Tamer Vestlund, Asli; Hewings, Geoffrey J. D.; Jordinson, Greg M.; Longhurst, Philip J.; Pollard, Simon J. T. (Elsevier, 2007)
We present bioaerosol source term concentrations from passive and active composting sources and compare emissions from green waste compost aged 1, 2, 4, 6, 8, 12 and 16 weeks. Results reveal that the age of compost has little effect on the bioaerosol concentrations emitted for passive windrow sources. However emissions from turning compost during the early stages may be higher than during the later stages of the composting process. The bioaerosol emissions from passive sources were in the range of 103–104 cfu m−3, with releases from active sources typically 1-log higher. We propose improvements to current risk assessment methodologies by examining emission rates and the differences between two air dispersion models for the prediction of downwind bioaerosol concentrations at off-site points of exposure. The SCREEN3 model provides a more precautionary estimate of the source depletion curves of bioaerosol emissions in comparison to ADMS 3.3. The results from both models predict that bioaerosol concentrations decrease to below typical background concentrations before 250 m, the distance at which the regulator in England and Wales may require a risk assessment to be comple
Keywords: Bioaerosols; Compost; Dispersion modelling; Emission rate; Exposure